2015
DOI: 10.1007/s10526-015-9678-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune defenses of Agriotes lineatus larvae against entomopathogenic nematodes

Abstract: The present work describes the immune response of wireworm larvae, Agriotes lineatus (L.) (Coleoptera: Elateridae) when challenged with two species of entomopathogenic nematodes (EPNs), Steinernema feltiae (Filipjev) (Strongyloidea: Steinernematidae) and Heterorhabditis bacteriophora (Poinar) (Rhabiditoidea: Heterorhabditidae). Two main immunological processes including cellular and humoral\ud reactions have been addressed. Total haemocyte counts after infection with H. bacteriophora increased quickly in initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…laumondii, were described from Iranian isolates of H. bacteriophora using 16S ribosomal RNA gene sequence and phenetic characters, which were collected from soil in Mashhad, Razavi Khorasan province, Iran (Karimi, Mokarm, & Hasani-Kakhki, 2012). Also, symbiotic bacteria of native H. bacteriophora from potato fields in Farooj, North Khorasan province, Iran and characterized as Photorhabdus luminescens based on main phenotypic and molecular characteristics (Rahatkhah et al, 2015). These results provide new insights for the biodiversity of bacto-helminthic complex in Iran.…”
Section: Isolates Of Symbiotic Bacteriamentioning
confidence: 81%
See 2 more Smart Citations
“…laumondii, were described from Iranian isolates of H. bacteriophora using 16S ribosomal RNA gene sequence and phenetic characters, which were collected from soil in Mashhad, Razavi Khorasan province, Iran (Karimi, Mokarm, & Hasani-Kakhki, 2012). Also, symbiotic bacteria of native H. bacteriophora from potato fields in Farooj, North Khorasan province, Iran and characterized as Photorhabdus luminescens based on main phenotypic and molecular characteristics (Rahatkhah et al, 2015). These results provide new insights for the biodiversity of bacto-helminthic complex in Iran.…”
Section: Isolates Of Symbiotic Bacteriamentioning
confidence: 81%
“…In a regional survey, two native isolate of EPNs, H. bacteriophora and S. feltiae were isolated from soil in Bojnourd, North Khorasan Province (Kamali et al, 2013). Moreover, during postharvest season of potato tuber, native EPNs were collected from potato fields in Farooj, North Khorasan province, Iran and characterized as H. bacteriophora and S. feltiae (Rahatkhah et al, 2015). These results indicated that the country has a rich fauna biodiversity resource of EPNs and therefore, it could be an opportunity for discovery of new nematode species and populations from other provinces.…”
Section: Basic Research On Entomopathogenic Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the rose sawfly Arge ochropus (Gmelin), the cellular responses were weaker to S. carpocapsae than in H. bacteriophora (Sheykhnejad et al 2014). In another study, 6% encapsulation of S. feltiae was reported, while it was 24% in H. bacteriophora in Agriotes lineatus (L.) (Rahatkhah et al 2015). Obtained results showed that the S. abbasi isolate CS 2 had the strong capability to avoid encapsulation responses in larval H. armigera leading to the death of larvae within a very short time.…”
Section: Resultsmentioning
confidence: 97%
“…arasbaranense (Nikdel et al, 2011) was described from East Azerbaijan province. Other surveys resulted in some already described species viz., S. glaseri, S. carpocapsae, S. bicornutum, S. kraussei (Karimi et al, 2009;Kary et al, 2009;Nikdel et al, 2008Nikdel et al, , 2010Ebrahimi and Niknam, 2011;Nikdel and Niknam, 2015;Rahatkhah et al, 2015).…”
Section: Pakistanmentioning
confidence: 99%